A boolean satisfiability approach to the resource-constrained project scheduling problem - Andrei Horbach (Universität Kiel, Institut für Betriebswirtschaftslehre, 2009)
We formulate the resource-constrained project scheduling problem as a satisfiabil-ity problem and adapt a satisfiability solver for the specific domain of the problem. Our solver is lightweight and shows good performance both in finding feasible solutions and in proving lower bounds. Our numerical tests allowed us to close several benchmark instances of the RCPSP that have never been closed before by proving tighter lower bounds and by finding better feasible solutions. Using our method we solve optimally more instances of medium and large size from the benchmark library PSPLIB and do it faster compared to any other existing solver.
Keywords: 650; Scheduling-Verfahren; Ganzzahlige Optimierung